1965
DOI: 10.1121/1.1909516
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of Low-Frequency Sonar Signals from a Smooth Ocean Bottom

Abstract: Measurements of the bottom-reflection losses for a low-frequency sonar signal (0.7–3.0 kc/sec) are reported for two areas off the California coast and for a third area in the Bering Sea. At all three areas, the bottom losses were large at small grazing angles. Comparisons are made between the measured values of bottom loss and those calculated for a plane sound wave reflecting from a layered model of the ocean sediments. The sediment model consists of a number of absorbing solid layers. Reasonable agreement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1970
1970
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This model shows good correlation with actual results in studies done by Bucker et al (2) and Anderson and Latham (1) in which several sets of viscoelastic constants are assumed and solutions are correlated with observed data. Although it has been demonstrated to be feasible and accurate, the viscoelastic model presents the difficulty of evaluating the Lame' constants for various oceanic areas and soft sediments.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…This model shows good correlation with actual results in studies done by Bucker et al (2) and Anderson and Latham (1) in which several sets of viscoelastic constants are assumed and solutions are correlated with observed data. Although it has been demonstrated to be feasible and accurate, the viscoelastic model presents the difficulty of evaluating the Lame' constants for various oceanic areas and soft sediments.…”
supporting
confidence: 81%
“…According to Morris (16), this is primarily due to neglect of the conversion of compressional wave energy into shear waves at the sediment interface and layer boundaries. For this reason a viscoelastic model is favored which uses complex Lame* constants and provides for the generation of shear waves upon reflection and for absorption of the waves (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting [4] into [1] we obtain: It is possible to write solutions to the equations of motion, [5], [6], and [7] for surface waves whose displace- (8) ik (x+r,Z) If c = 3, the left-hand side of [10] is equal to 1, while 2 2 for c = it becomes -16(1-3 /a ) which is less than 0.…”
mentioning
confidence: 99%
“…(1) the Stonely wave technique [10], which is limited to low frequencies; (2) use of torsional wave vibration [7]; or (3) a torsional wave viscoelastometer [11,5,2]. 8 Research conducted by Hutchins [11] at the Naval Postgraduate School demonstrated the feasibility of measuring the complex shear modulus or dynamic rigidity of simulated ocean sediments.…”
Section: For This Reason a Viscoelastic Model Involving Complex Lame mentioning
confidence: 99%